Development and application of green and sustainable analytical methods for flavonoid extraction from Passiflora waste - Danielle da Silva Francischini (BMC Chemistry, 2020)
Abstract Brazilian biodiversity and favourable environmental conditions open up possibilities not yet explored, showing potential to shift the country’s monochromatic economy into an emancipated, diversified and sustainable economic environment. This can be made possible through the integral use of its resources, exploring every functional fraction to create novel solutions to modern problems. Biorefineries present an interesting strategy to fully use the potential of agricultural feedstocks and together with green separation methods can contribute to the generation of sustainable processes and products. Passion Fruit (Passiflora edulis Sims f. flavicarpa Deg species) is produced on a large scale in Brazil and in other tropical countries, and its processing plants generate tons of residues that basically consist of peel, seeds and bagasse, which account for around 75% of its mass. These fractions of P. edulis can contain significant amounts of flavonoids, secondary metabolites that are the main compounds responsible for the fruit’s bioactivity (antioxidant, anti-inflammatory, pesticide and biocide, in general). Therefore, this work aims to develop, apply and compare the best conditions for the extraction of isoorientin, orientin and isovitexin from passion fruit applying solid–liquid methodologies, followed by analyte quantification using UHPLC-PDA. Homogenizer-assisted (HAE), ultrasound-assisted (UAE) and microwave-assisted (MAE) extraction techniques were used, as well as a full factorial design to reach optimal parameters concerning the extraction yield and energy and solvent efficiencies. According to the results, the procedure based on HAE presented the best conditions for the extraction of selected flavonoids (1.07, 0.90 and 0.33 mg g−1 of isoorientin, orientin and isovitexin, respectively) and was considered the best method according to the green and sustainable described factors.